Educação musical e a promoção do letramento emergente de crianças em risco psicossocial - Fantini, Renata Franco Severo (Universidade Federal de São Carlos, 2013)
The studies have shown that learning music encourages the global development of a child. Recent studies have shown the benefits of musical education towards the development of phonological awareness and the conventions and conceptions of writing for children with special needs and children at risk. Given the importance in our area, the search for innovative practices for musical development and emergent literacy in a school context, the current study has as its objective verifying the effects of the interdisciplinary program including the musical skills and abilities that promote reading and writing skills such as phonological awareness and knowledge about the functions and conventions of writing. The participants were three children who were enrolled in First Grade in Elementary School with a history accentuated by hardships in life. For fourteen meetings, the students participated in activities directed towards musical perception, rhythm and beat, general music knowledge, interest for literature and handling books and writing concepts. The study consisted of comparing the percentages of right answers of skills tested before and after participation in the program. Tests were used to evaluate musical skills, phonological awareness and emergent literacy. The results indicated that some skills had a moderate to high increase in the percentage of correct answers and other skills did not show improvement. Corroborating with the findings of previous studies in this area, we can conclude that the interdisciplinary program conducted in this study favored the promotion of musical skills and emergent literacy. This research contributes both to a new line of research and to the possibility of the Music teacher working along with the Preschool Education and the first grade of Elementary School in order to explore a promising perspective of interdisciplinary work in music and emergent literacy process.
Keywords: Educação especial; Educação musical; Consciência fonológica; Letramento emergente; Musical education; Emergent literacy; Special education; Phonological awareness; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL